Modelagem MDD de Frameworks SPA: uma evolução do método FrameWeb - Hoppe, Pedro Henrique Brunoro (2023)
In the field of Web Engineering, many methods have been proposed to guide developers in designing and coding Web applications. The FrameWeb method is a model-driven approach that targets the development of systems that use certain kinds of frameworks in their architecture, proposing the use of models that incorporate concepts from these frameworks during design. For the time being the FrameWeb method currently does not consider SPA (Single Page Application) frameworks and, in recent years, such kind of framework has gained a lot of popularity among developers. In this work, we propose to add support for SPA frameworks to FrameWeb. This work was conducted under the context of Design Theory, in particular applying the Design Science Research method to propose such solution. With our research, we have managed to updated the FrameWeb meta-model so that its modeling language now supports SPA frameworks and their constructs. FrameWeb tools (graphical editor and code generator) also evolved to support the new elements. Experiments of modeling existing SPAs with this new version of FrameWeb, generating code from the models and comparing with the original showed that, in average, around 69% of the HTML tags could be generated from the models. The support for SPA frameworks in FrameWeb allows developers to design and model their applications using constructs that relate to the frameworks used in the development, facilitating developer communication using the models and generating code to improve developer productivity.